Triglyceride-glucose index mediates the association between residual cholesterol and stroke among middle-aged and older adults in China: a prospective, nationwide, population-based study - Li, Xu; Hu, Jia-Guang; Liao, Qian; Wu, Ying; Huo, Rong-Rui (Frontiers in Cardiovascular Medicine, 2024)
BackgroundBoth triglyceride-glucose (TyG) index and residual cholesterol (RC) are predictors of stroke; however, to what extent the RC is associated with stroke through TyG index is unclear. This study examined whether the TyG index mediates the association of RC with incident stroke and the extent of interaction or joint relations of RC and TyG index with stroke in middle-aged and older Chinese adults.MethodsThis is an ongoing prospective cohort study initiated in 2011 that included 10,569 middle-aged and older Chinese adults without stroke at baseline. The exposure was RC, the mediator was TyG index, and the outcome was stroke which followed up from June, 2011, to June, 2018. Mediation analysis was used to explore whether the TyG index mediated the association between RC and stroke risk.ResultsOf the 10,569 participants, 4,978 (47.1%) were men; the mean (SD) age was 59.01 (9.43) years. During a median follow-up of 7.1 years, 734 (7.0%) participants experienced a stroke. In the adjusted Cox models, A one SD increase in RC was associated with an elevated risk of stroke (HR, 1.09; 95% CI, 1.02–1.16), as well as TyG index (HR, 1.14; 95% CI, 1.06–1.23). No significant multiplicative or additive interactions were found between the TyG index and RC on stroke risk (HR for multiplicative: 1.07, 95% CI, 0.67–1.70; Synergy index: 1.05, 95% CI, 0.16–6.88). TyG index mediated the association between RC and stroke (b, −0.16; 95% CI, −0.30 to −0.03). Subgroup analyses and sensitivity analyses showed consistent results.ConclusionsThis study evidence that the TyG index completely mediates the association between RC and stroke risk among middle-aged and older Chinese adults. These findings highlight the importance of considering RC and the TyG index in stroke risk assessment.